Universities and economically depressed regions: how `attractive' is the University of Évora? - António Caleiro; Conceiç\~ao Rego (European Regional Science Association (ERSA), 2004)
As it is well known, universities constitute sources of important multiplier effects on the economic activity of the regions where they are located. Plainly, in the case of economically depressed regions, the importance of universities becomes higher. This is certainly the case with the University of Évora as being located in the Alentejo, one of the poorest regions at the European Union level, it have been contributing to the attraction of economic activity. Besides the direct effect on the economic activity of the Alentejo, the University of Évora also have been exerting demographic effects, on the one hand, by allowing people to become residents on the region and, on the other hand, by attracting students which normally become residents during the period of time required to conclude their academic degrees. The paper explores this last effect by the analysis of how and why the University of Évora is chosen by students coming from all over the country (and from abroad). This analysis, which is done through the use of econometric techniques, also indicates which are the decisive factors for the attraction exerted by the University of Évora, in general, and by its degree courses, in particular, on the candidate students. KEYWORDS: Decision Analysis, Discrete Choice Models, Portugal, Universities JEL CLASSIFICATION: C21, R12, R23
Keywords: C21; R12; R23; 330; Decision Analysis; Discrete Choice Models; Portugal; Universities